2013
DOI: 10.4081/ijfs.2013.e24
|View full text |Cite
|
Sign up to set email alerts
|

Variability of cadmium accumulation in cephalopods (Octopus vulgaris, Sepia officinalis, Loligo vulgaris and Todarodes sagittatus) collected in Sardinia in 2008-2012

Abstract: Cephalopods are known to accumulate cadmium and play an important role in its biomagnification. They are an essential link in marine trophic chain and represent an important case in studies on cadmium transfer to man through the food chain. Since cadmium concentration widely varies in different tissues of the cephalopods – mainly accumulating in the hepatopancreas – evisceration represents a recommended preliminary step to reduce cadmium intake in view of cephalopods consumption; yet, the residual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
2
1
0
Order By: Relevance
“…Cadmium concentrations in muscle and digestive gland in the present study were comparable with those previously reported by other authors [10,17].…”
Section: Resultssupporting
confidence: 93%
“…Cadmium concentrations in muscle and digestive gland in the present study were comparable with those previously reported by other authors [10,17].…”
Section: Resultssupporting
confidence: 93%
“…Being this class composed primarily by cephalopods, which is the main species of molluscs imported through BIP of Milan Malpensa, these results agree with those of Bustamante, Caurant, Fowler, and Miramand (1998), Pastorelli et al (2012), Morgano, Rabonato, Milani, Miyagusku, and Quintaes (2014) and Piras, Chessa, Cossu, Rubattu, and Giori (2013); these authors considered cephalopods as a significant Cd source. For O. vulgaris from Morocco, Egypt, Tunisia, we obtained a median value of 25 mg kg À1 for Cd, of 20 mg kg À1 for Hg and of 33 mg kg À1 for Pb; very similar concentrations were reported by Chahid, Filali, Benlhachimi, & Bouzid (2014), for the same FAO fishing area (Atlantic Ocean, Morocco): he obtained values of 20 mg kg À1 for Cd, 49 mg kg À1 for Hg and 45 mg kg À1 for Pb.…”
Section: Discussionsupporting
confidence: 92%
“…The most distinctive feature that become evident from this study was the significantly higher bioaccumulation of Cd in flying squids compared to European squids. The amount of Cd found was in the same order of magnitude as that reported by Piras et al (2013), but, contrary to our results, these authors did find equal concentrations also in muscular tissues of Loligo vulgaris samples. Conversely, higher concentrations (up to 8.5 mg/kg) were measured in Todarodes Sagittatus than in Loligo vulgaris samples by Miedico et al (2015).…”
Section: Discussioncontrasting
confidence: 93%